Social network moderators of the association between Ghanaian older adults' neighbourhood walkability and social activity - Asiamah, Nestor; Conduah, Andrew Kweku; Eduafo, Richard (Health promotion international, 2021)
This study examined the moderating influences of active social networks (ASN), sedentary social networks (SSN) and ASN lost on the relationship between neighbourhood walkability and social activity in community-dwelling older adults aged 60 years or more in Accra, Ghana. A total of 863 individuals participated after G*Power 3.1 was utilized to calculate the minimum sample size. We analysed the data with Pearson's correlation test and hierarchical linear regression models. A sensitivity analysis was conducted to select the ultimate confounding variables. The study found a positive influence of neighbourhood walkability on social activity after the covariate adjustment (β = 0.18; t = 5.2; p = 0.000). The positive influence of neighbourhood walkability on social activity was significantly reduced by ASN lost and SSN. ASN did not have a significant moderating influence on the primary relationship. The study concludes that the positive influence of walkable neighbourhoods on social activity decreases as SSN and ASN lost increase.